Impact of different exercise intensities on pregnant rats and on their offspring - Netto, Aline O. [UNESP]; Dias Macedo, Nathália C. [UNESP]; Gallego, Franciane Q. [UNESP]; Sinzato, Yuri K. [UNESP]; Volpato, Gustavo T.; Zambrano, Elena; Damasceno, Débora Cristina [UNESP] (FapUNIFESP (SciELO), 2020)
This study aimed at evaluating the levels of different maternal exercise intensities on maternal and fetal outcomes. Wistar rats were mated and the pregnant rats were distributed into four experimental groups (n = 13 animals/group): Control (Not exercise group-0% of the anaerobic threshold-AT), mild (20%), moderate (80%), and heavy-exercise intensity (140% of AT). These AT were matched to the load of 0, 1, 4 and 7% of the body weight of the animal related to swimming-induced physical intensity. In pregnancy, biomarkers related to maternal blood gases, oxidative stress, metabolism, and reproductive performance, and outcomes of their offspring were analyzed. The mild and moderate-swimming caused no change on implantation, live fetus numbers and oxidative stress status. However, the rats submitted to mild-exercise presented respiratory alkalosis and the heavy-exercise group showed respiratory acidosis. In addition, fetuses of the heavy-exercise dams were smaller for gestational age and lower serum adiponectin levels compared to those of other groups. In conclusion, the moderate-exercise intensity caused beneficial effects for maternal environment and the mild and moderate-exercise presented similar fetal repercussions. Nevertheless, the heavy-exercise intensity caused maternal metabolic alterations that damaged the fetal growth. Therefore, these findings confirm that physical intensity should be carefully conducted to avoid maternal complications and, consequently, compromised fetal repercussions.
Keywords: Exercise intensities; Fetuses; Pregnancy; Swimming